Survei Kecepatan Tendangan Sabit Pencak Silat Pada Atlet Pusat Pendidikan dan Latihan Olahraga Pelajar (PPLP) Maluku Utara - Triana Nuryastuti; Irmayani Upara (Peneliti.net, 2023)
This study aims to determine the speed of sickle kicks of athletes from the North Maluku Student Education and Training Center (PPLP). The research was conducted using survey methods or through observation tests and sickle kick speed skills tests directly in the field. The research was conducted at PPLP GOR with a sample of 10 people. The research subjects were the male and female athletes of PPLP North Maluku. Data analysis used descriptive statistical techniques in the form of percentages. The results of the data analysis show that of the 10 athletes with a test time of 10 seconds with sickle kick results, 5 male athletes with a score of 60 and above are included in the very good category as much as 1 person or 20%, with a score of 57-59 including the good category none or by 0%, for a score of 53-56 the category is enough for 3 people or by 60%, for a score of 49-52 the category is lacking by one person or by 20%, and for the very poor category with a score of 48-down either none or by 0%. Whereas for 5 female athletes, with a score of 54 and above, they are included in the Very Good category, none or 0%, for a score of 50-53, one person is good or 20%, for a score of 44-49, 3 people are in the sufficient category. or by 60%, for a score of 49-52 the category is lacking by one person or by 20%, and for the very poor category with a score of 38 and below there is none or by 0%. Based on the results of the analysis, it was concluded that the ability of sickle kick speed for male and female athletes of PPLP North Maluku was included in the average average category with a percentage of 60%.